Analisis Penggunaan Sistem Informasi Akuntansi Dalam Mendukung Keberlanjutan Bisnis - Nurul Laily Oktaviani; Shirky Kharisma Fitri Hasnita; Irda Agustin Kustiwi (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to analyze the use of accounting information systems in supporting business sustainability. This study uses a qualitative approach with data collected from several companies that have implemented accounting information systems. The research results show that accounting information systems have a vital role in increasing operational efficiency, reducing risk, and supporting sustainable decision making.